Love, Danielle [videorecording (DVD)] - Sears, Steve; Sidell, Devin; Sidell, Devin; King, Jamie Thomas, 1981-; Warren, Lesley Ann; Roark, Michael, 1983- (Freestyle Digital Media, 2025)
Family dysfunction collides with a woman's decision to have preventative surgeries to reduce her risk of developing cancer.